2017
DOI: 10.1097/spv.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Personality Traits on Psychological Distress in Women With Pelvic Floor Disorders

Abstract: Our suggested statistical path analysis model supports the important role of personality traits in pelvic floor disorder self-reports and the effect of these traits on psychological distress. Therefore, the optimal treatment for pelvic floor symptoms should include psychological interventions in addition to traditional medical or surgical therapy in hope of reducing psychology distress associated with urinary incontinence and pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…To our knowledge, the present study is the first empirical study that has examined the cross-cultural difference in the relationship between personality traits and neurasthenia. Using a longitudinal design, we found that neuroticism was positively related to neurasthenia, which is in line with prior findings that neuroticism is casually related to some illnesses (Cramer et al, 2016; Liu et al, 2018; Yaakobi et al, 2017). However, inconsistent with the prior cross-cultural findings about the relationship between adolescents’ personality and mental and physical health (Liu et al, 2018), our data did not reveal significant cross-cultural differences in the relationship between personality and neurasthenia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, the present study is the first empirical study that has examined the cross-cultural difference in the relationship between personality traits and neurasthenia. Using a longitudinal design, we found that neuroticism was positively related to neurasthenia, which is in line with prior findings that neuroticism is casually related to some illnesses (Cramer et al, 2016; Liu et al, 2018; Yaakobi et al, 2017). However, inconsistent with the prior cross-cultural findings about the relationship between adolescents’ personality and mental and physical health (Liu et al, 2018), our data did not reveal significant cross-cultural differences in the relationship between personality and neurasthenia.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between personality and health is an old research topic. A number of empirical studies have found that personality is significantly related to both mental and physical health (Cramer et al, 2016; Yaakobi et al, 2017). In a recent cross-cultural study, Liu et al (2018) found that there are some cross-cultural differences in the relationship between adolescents’ personality and mental and physical health.…”
mentioning
confidence: 99%
“…In a sample with mixed pelvic floor disorders, trait optimism predicted subjective report of pelvic floor symptoms, such that those with greater trait positive expectancy reported less symptoms and less distress related to symptoms [124]. The ability of positive expectancies to predict treatment outcomes in POP should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was part of a larger project [19] conducted in an urogynecology outpatient clinic of a major tertiary medical center between August 2014 and June 2015. On randomly selected clinic days, a research assistant approached the women attending the clinic.…”
Section: Methodsmentioning
confidence: 99%